2023
DOI: 10.4102/safp.v65i1.5684
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to voluntary medical male circumcision as an HIV prevention strategy in Kavango East, Namibia

Abstract: Background: Voluntary medical male circumcision (VMMC) is a strategy used to try to limit new human immunodeficiency virus (HIV) infections, as it has the potential to reduce HIV and/or AIDS transmission from women to men by up to 60%. However, in spite of efforts by the Ministry of Health and Social Services, only a few men in Namibia have been circumcised. The objective of this study was to explore and describe the facilitators of, and barriers to, medical male circumcision for HIV prevention in Kavango East… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Tusabe, et al, [67] in a study conducted in 2020, found that fear of pain and compulsory HIV testing, long healing time, financial constraints, perceived interruption of God's plan, loss of male fertility and involvement of female health workers were barriers to VMMC. Another study also conducted in 2020 in Namibia, found that myths and misconceptions attached to VMMC, age limitations, fear of pain and stigma associated with HIV, and long distances from health facilities negatively impacted VMMC uptake [68].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Tusabe, et al, [67] in a study conducted in 2020, found that fear of pain and compulsory HIV testing, long healing time, financial constraints, perceived interruption of God's plan, loss of male fertility and involvement of female health workers were barriers to VMMC. Another study also conducted in 2020 in Namibia, found that myths and misconceptions attached to VMMC, age limitations, fear of pain and stigma associated with HIV, and long distances from health facilities negatively impacted VMMC uptake [68].…”
Section: Plos Global Public Healthmentioning
confidence: 99%